Pengaruh Pembelajaran Kooperatif terhadap Kreativitas Peserta Didik: Studi Implementasi di Lingkungan Sekolah - Anandita, Septian Ragil; Permatasari, Yovita Dyah; Hayati, Irma Nur; Huda, Nurul; Afif, Mohammad Choiron; Setiawan, Budi; Fajriani, Siti Qoniah; Firnanda, Putri Mey; Putri, Niken Koeswara (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2025)
This article discusses community service activities in Ngusikan Village through a cooperative learning method implementation program. Cooperative Learning is a form of learning in which students learn and work in small groups collaboratively with different levels of ability whose members consist of four to six people with a heterogeneous group structure. The aim of this program is to apply a variety of learning methods, in order to create a learning atmosphere that is not boring for students. Motivate teaching staff to be able to utilize learning media other than worksheets or textbooks, so that the learning process is more interesting and enjoyable.